1998
DOI: 10.1055/s-2008-1043907
|View full text |Cite
|
Sign up to set email alerts
|

Das differenzierte Schilddrüsen-Karzinom bei Kindern und Jugendlichen

Abstract: Differentiated thyroid cancer is a rare disease in childhood and adolescence. Most frequently, thyroid cancer in children belongs to the papillary variant, whereas a follicular histological pattern is much less frequently encountered. Dedifferentiated (anaplastic) cancers are very rare at this age. Especially indolent cervical lymph node enlargement is suspicious for a thyroid cancer, even more when occurring together with a solitary, rapidly growing, and indurated thyroid nodule. Every nodule in the thyroid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Their study, like ours, showed that none of the nonoperated-on patients reached the point of one-year survival. Multiannual survival in patients with complete resection of the tumour occurs irrespective of the extent of operation on the thyroid, that is, irrespective of the fact whether a total thyroidectomy or only hemithyroidectomy was performed, the only condition being that the tumour was totally removed [11]. According to Venkatesh et al [13], surgery is vital but not sufficient enough for longer survival, as one-year survival is noted in operated-on patients but almost never in nonoperated-on ones, and radical operation without multimodal treatment does not significantly prolong the survival.…”
Section: Discussionmentioning
confidence: 99%
“…Their study, like ours, showed that none of the nonoperated-on patients reached the point of one-year survival. Multiannual survival in patients with complete resection of the tumour occurs irrespective of the extent of operation on the thyroid, that is, irrespective of the fact whether a total thyroidectomy or only hemithyroidectomy was performed, the only condition being that the tumour was totally removed [11]. According to Venkatesh et al [13], surgery is vital but not sufficient enough for longer survival, as one-year survival is noted in operated-on patients but almost never in nonoperated-on ones, and radical operation without multimodal treatment does not significantly prolong the survival.…”
Section: Discussionmentioning
confidence: 99%